WEB SEARCHING AN ART - Chinu; Gupta, Ramil; Ekta (International Journal of Computer Sciences and Engineering, 2025)
In today’s world searching information over the internet is one of the difficult task. Specialized tools called search engines plays an important role to retrieve information from world wide web. There are many of search engines available today but retrieving meaningful information is difficult. However to overcome this problem in search engines to retrieve meaningful information intelligently, semantic web technologies are playing a major role. In this research work we present a study on the search engine generations and the role of search engines in intelligent web search technologies.